The Habit in Cohabitation: (Or, How to Meet a Tiger on the Path) - Weston, Kath (Humanimalia, 2022)
As human and nonhuman animals increasingly share space, however enthusiastically or reluctantly, the concepts of habit, cohabitation, and habituation bear further scrutiny when applied to these makeshift arrangements. Even when researchers have critically examined the work these terms do in discussions of more-than-human relations, they have tended to ignore the temporalities embedded in "habit" and its cognates. A discourse of habit traps animals in an ethnographic present of the sort long critiqued within anthropology in its application to humans. One alternative is to approach more-than-human animals as what Mahesh Rangarajan calls "animals with histories," instead of treating them as members of species with fairly set characteristics who make cameo appearances in ecological histories, ethnographies, and field studies. Studies of human-tiger relations in Rajasthan, India, and auto-ethnographic material on human-bear relations in Alaska suggestively illustrate what a historical orientation has to offer by way of moving discussions of multispecies relations beyond a colonial discourse of encounter and the blurring of human/nonhuman boundaries. Acknowledgment that nonhuman animals have historically inflected backstories, even when their memories and experiences are not accessible to humans, is a step in the direction of more expansive possibilities for co-worlding.